Marriage at the Foot of the Great Wall, in the Land of the Rising Sun and on the Banks of the Ganges – Chinese, Japanese and Hindu Marriages - István, Kasuba Róbert (Nurani Hukum, 2024)
This research explores the legal systems of China, Japan, and India, focusing on their transition from customary to codified law, shaped by European colonialism and Christian missionary activity. Specifically, it examines how matrimonial law in these countries remains primarily governed by common law rather than codified statutes. The study emphasizes the role of customary religious law, analyzing its ongoing influence despite the adoption of codified legal frameworks. Using a comparative method, the research traces how the legal systems of China and Japan evolved similarly, influenced by German and French legal traditions, while India's system reflects the impact of British colonialism and English common law. This analysis contributes to understanding the intersection of civil marriage, religious rights, and legal traditions, providing insights into the enduring relevance of customary and religious practices in modern legal systems. The findings are crucial for further exploring the potential introduction of optional civil marriage in these countries.